2022
DOI: 10.3389/fenrg.2022.915893
|View full text |Cite
|
Sign up to set email alerts
|

Review of Unconventional Natural Gas Liquefaction Processes

Abstract: Liquefied natural gas (LNG) has become an important part in the energy industry on account of its high energy density, low carbon emission, and convenient transportation. In recent years, with the discovery of unconventional natural gas resources, the situation of the world’s natural gas liquefaction plants using conventional natural gas as feedstock is changing. Unlike traditional LNG plants, unconventional natural gas liquefaction processes require special considerations in design and manufacturing. This rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Table 3 shows the equipment and methods used for determination of the composition and characteristics of NGL samples and products of their processing on a zeolite catalyst. ±0.9 kg/m 3…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 3 shows the equipment and methods used for determination of the composition and characteristics of NGL samples and products of their processing on a zeolite catalyst. ±0.9 kg/m 3…”
Section: Methodsmentioning
confidence: 99%
“…Gas is used to generate heat and electricity, and also as a fuel for transport [1]. The popularity and environmental friendliness of natural gas are the reasons for the steadily growing demand for this type of fuel [2,3]. That is why the search for and development of new natural gas fields are being actively conducted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural gas, a prominent, high-quality, and eco-friendly energy source, plays a significant role in the global energy structure, accounting for approximately 23% of the total energy consumption (Xu et al, 2022). Following extraction, natural gas undergoes liquefaction to facilitate its storage and transportation.…”
Section: Introductionmentioning
confidence: 99%
“…Some zero-emission ships using hydrogen, ammonia and biofuel lack the infrastructure capacity and comprehensive specifications to satisfy the world shipping needs (Depken et al, 2022) while CO 2 emissions of the other marine fuels are shown in Figure 1. Liquefied natural gas (LNG), a kind of clean energy with high energy and fuel efficiency (Burel et al, 2013;Xu et al, 2022), has the lowest CO 2 emissions in Figure 1, at least 20% less than traditional oil fuel (DNV, 2019;Sharples, 2019). LNG has virtually no SOx and very low particulate emissions, whose NOx emissions requirements (Lindstad and Rialland, 2020).…”
Section: Introductionmentioning
confidence: 99%